Methodological proposal for the analysis of the health situation. - Sara Hernández Malpica; Laura López Angulo; Inés Domínguez Silva (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2003)
A methodology for analysing the health situation is carried out in this search, taking into account that the existing guides do not give an appropriate response to the present demands that such an analysis requires either in the students, residents and specialists, trying to keep the determinants of the health state of the population. Generally there are differences due to the fact that the gathered information can not be enclosed in the corresponding category. This research was carried out at the Cienfuegos School of medicine from October to December 2002. Documental observation was used for both the analysis of the contents of the existing guides and for the student´s literature related to these contents. The acceptance of the professors, pre-graduate students and residents shows that this document is useful for its assignment and for the analysis of the consultation offices and of the health areas. Although it is impossible to express the economic value of this search, it has social implications since it contributes to improve the quality of the teaching learning process.